French : phrasebook & CD (Australia : Lonely Planet, 2015)
Your handy passport to culturally enriching travels with the most relevant and useful French phrases and vocabulary for all your travel needs. Ask about tucked-away vineyards, bargain with local farmers at the market or order wine like a professional; all with your trusted travel companion. The Audio CD includes 375 key phrases and can be downloaded as an MP3.
Audio CD
Keywords: French language -- English -- Conversation and phrasebooks; French language -- Dictionaries -- English; French language -- Sound recordings for English speakers